Nano-encapsulation of proteins and peptides - Ibrahim Ali, Noorbatcha; Jaswir, Irwandi; Ahmad, Hasna (Bentham Science, 2017)
The significance of protein and peptide use as therapeutic agents in parallel with conventional drugs has long been established with the use of insulin, growth hormones and antibiotics for treatment of diseases. Proteins and peptides offer high specificity, precise function and low immune response from the body. These therapeutic molecules are administered via intravenous and subcutaneous injection, oral administration and nasal inhalation. However, their macromolecular size and high susceptibility to degradation in the body when administered hamper their effective delivery and action. Nanoencapsulation of proteins and peptides is an attractive strategy to improve the stability of proteins and peptides and maintain activity at the target site. Encapsulation into nanoparticles ensures that the proteins and peptides are more stable, bioavailable and more effective due to sustained release and targeted delivery; the smaller size equals larger surface area to volume ratio allows for better absorption in the intestinal lumen. However, challenges are still present in formulating nanoparticles with desired physicochemical properties for their effective action and sustained release. The need for case- by case formulation of protein/ peptide, limitations in the available methods for fabrication, characterization and analysis of the nanoparticles, as well as difficulty in translating lab- scale research into commercial stage are the current problems that need to be addressed. Furthermore, it is important to assess that nanoparticle formulations are commercially sustainable next to free form drugs. Many gaps need to be filled in understanding the nature of proteins and peptides, their fabrication into nanoparticles, and successful translation into clinical products. Continued focus into research in these areas is the way forward for the future of protein and peptide delivery.